Síntese estereosseletiva dos alcaloides tetra-hidroquinolínicos (S)- e (R)-galipeína, (S)-cuspareína, (S)-galipinina e (S)-angustureína - Nilton Gonçalves da Cruz (2022)
Alkaloids are a class of compounds in which there is great interest in their studies because they have biological activity. Galipea officinalis Hancock is a shrub found in Venezuela and produces 1,2,3,4-tetrahydroquinoline alkaloids (THQs) angustureine, cuspareine, galipinine and galipeine, also known as Hancock alkaloids. These compounds were showed to present antimalarial activity in vitro. Enantioselective synthesis of these alkaloids through varied synthetic routes have been published, only three of them with protocols involving enzymatic kinetic resolution. In this work, the enantioselective synthesis of Hancock alkaloids was performed through esterification and reduction of quinaldinic acid, followed by enzymatic kinetic resolution of the formed alpha-amino and then a Wittig reactions followed by hydrogenation. In the enzymatic resolution step, we used a hydrolysis reaction catalyzed by commercial immobilized Candida antartica lipase B and obtained the intermediate (R)-α-amino ester and the corresponding (S)-carboxylic acid. The (S)-α amino ester was prepared through the esterification of the (S)-carboxylic acid produced in the hydrolysis. The (R)-α-amino ester and (S)-α-amino ester were produced with 94% and 71.4% enantiomeric excess and 40% and 22% yield, respectively. The alkaloids (S)-angustureine, (S)-cuspareine, (S)-galipinine and (R)- and (S)-galipeine were synthesized with 80, 74, 67, 57 and 72% enantiomeric excess and 37, 34, 34, 32 and 34% overall yield, respectively. The decrease of the ee of the final products in comparison to the ee of the chiral intermediates corroborates with a racemization process.